Smart Partnership Program: Seiring Menuju Puncak Menara - Mohd Firdaus, Mohd Kamaruzaman (Pusat Bahasa Moden dan Sains Kemanusiaan, 2012)
3 April 2012. A one-day Smart Partnership Program in collaboration with SMK Tengku Abdullah was held at Mini Theatre and MML 10 and 11, Block X. The program was initiated in order to foster relationship between UMP and SMK Tengku Abdullah and to expose the school students to UMP learning environment.